How to catalouge : a practical handbook using AACR 2 and library of congress - Chapman, Liz. (New Delhi : USB publishers distributors limited, 1990)
A practical manual describing standard procedures in cataloguing using AACR2 1988 Revision and Library of Congress cataloguing data. It covers both the use of data generated from a centralized source and original cataloguing. Procedures are described for both manual and automated systems.
includes index.
Keywords: Library of Congress -- Subject Cataloging Division; Library of Congress Subject Headings -- Handbooks, manuals, etc; Cataloging; MARC formats -- United States